Mechanisms of AT(1a) receptor-mediated uptake of angiotensin II by proximal tubule cells: a novel role of the multiligand endocytic receptor megalin - Li, Xiao C. (American Physiological Society, 2014)
The present study tested the hypothesis that the multiligand endocytic receptor megalin is partially involved in the uptake of ANG II and downstream signaling responses in mouse proximal tubule cells (mPCT) by interacting with AT(1a) receptors. mPCT cells of wild-type (WT) and AT(1a) receptor-deficient (AT(1a)-KO) mice were treated with vehicle, the AT(1) receptor blocker losartan (10 μM), or a selective megalin small interfering (si) RNA for 48 h. The uptake of fluorescein (FITC)-labeled ANG II (10 nM, 37°C) and downstream signaling responses were analyzed by fluorescence imaging and Western blotting. AT(1a) receptors and megalin were abundantly expressed in mPCT cells, whereas AT(1a) receptors were absent in AT(1a)-KO mPCT cells (P < 0.01). In WT mPCT cells, FITC-ANG II uptake was visualized at 30 min in the cytoplasm and in the nuclei 1 h after exposure. Losartan alone completely blocked the uptake of FITC-ANG II, whereas megalin siRNA inhibited only 30% of the response (P < 0.01). The remaining FITC-ANG II uptake in the presence of megalin siRNA was completely abolished by losartan. ANG II induced threefold increases in phosphorylated MAP kinases ERK1/2 and a onefold increase in phosphorylated sodium and hydrogen exchanger 3 (NHE3) proteins, which were also blocked by losartan and megalin-siRNA. By contrast, losartan and megalin siRNA had no effects on these signaling proteins in AT(1a)-KO mPCT cells. We conclude that the uptake of ANG II and downstream MAP kinases ERK1/2 and NHE3 signaling responses in mPCT cells are mediated primarily by AT(1a) receptors. However, megalin may also play a partial role in these responses to ANG II.